Working Capital Planning at PT Kelola Lingkungan Kita as an Effort to Increase Probability - Alie Sutjiadi; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Diana Fajarwati (Journal of Multidisciplinary Academic, 2020)
PT Kelola Lingkungan Kita (PT KLK) is an integrated hazardous waste management company, covering services in the sectors of transportation, collection, processing and utilization of B3 waste with working areas such as Sumatra, Java, Kalimantan, Nusa Tenggara and Bali. As a new company, PT KLK needs to see the effectiveness of its capital in order to obtain profits as planned. This study aimed to know the efficiency in working capital planning at PT KLK as an effort to increase probability. In this study we used descriptive quantitative which means the data observation is describing by collected data without intending to make general conclusions. The results of this study are PT. KLK must optimize capital turnover in the following years. The result is that efficiency in the use of capital is still not good.